The effect of income inequality on the incidence of index crime a study on the Philippine setting - Chu, Lawrence Niccolo G. (School of Economics, University of the Philippines Diliman, 2019)
The goal of this paper is to revisit the impact of income inequality on the index crime rate at the provincial level of the Philippines by utilizing panel data. Given the change in method of nationwide crime reports in 2009, our analyses exploit data specifically from the Human Development Report (HDR) and the Family Income and Expenditure Survey (FIES), containing the Gini Coefficient and crime statistics for the 81 local provinces over the period of 2006 and 2009. We mainly used and compared three econometric methods to determine the relationship of the Gini Coefficient and index crime rate _ ordinary least squares (OLS), Fixed Effects (FE), and Random Effects (RE). By utilizing the Hausman Specification Test, the Random Effects model proved to be more accurate than the Fixed Effects model. After controlling for the variables of education, population density, poverty, unemployment, and real income, the results suggest that a 1_point increment in the Gini Coefficient may lead to an increase of 4 instance of index crime per 100,000 population. Other variables that were found to be significant are the mean years of schooling and the population density.